Supplementation with Complex Phytonutrients Enhances Rumen Barrier Function and Growth Performance of Lambs by Regulating Rumen Microbiome and Metabolome - Juan Du; Yuan Wang; Shaohui Su; Wenwen Wang; Tao Guo; Yuchao Hu; Na Yin; Xiaoping An; Jingwei Qi; Xuan Xu (Animals)
Complex phytonutrients (CPS) have attracted extensive interest due to their anti-inflammatory effects. This investigation focused on the impact of CPS on rumen health in lambs on high-concentrate diets, emphasizing growth performance, ruminal fermentation, epithelial barrier integrity, ruminal metabolism, and microbial communities. A total of 54 lambs, 3 months old and with a 30.42 ± 0.54 kg body weight, were randomly assigned to three treatment groups, with six replicates per treatment and three lambs per replicate. The lambs received a basal diet (the ratio of concentrate to forage was 75:25) without CPS supplementation (CON) or with the inclusion of 2.5 g/kg (CPS2.5) or 5.0 g/kg CPS (CPS5.0) for a total of 60 days. The CPS groups exhibited increased growth performance and improved rumen fermentation parameters. Mechanistically, CPS enhanced rumen epithelial barrier function, thereby lowering inflammation and inhibiting the overactivation of the JNK/p38 MAPK signaling pathway, and the effect of CPS5.0 was better than that of CPS2.5. Notably, CPS5.0 could optimize the composition of rumen microbiota and increase the levels of Ursolic acid and other metabolites. The strong associations between rumen bacteria and health-related indicators and differential metabolites were further highlighted. Our findings suggest that adding CPS to lambs’ diets has widespread positive impacts, including improved growth performance, reduced inflammation and mRNA relative expression of apoptosis-related genes, enhanced barrier function, and beneficial changes in the rumen microbiome and metabolite profiles.